Ecology of culture: landscape approach - O. D. Rykhlytska (Ukrainian Cultural Studies, 2017)
The article represents the analysis of the philosophic-culturalaspects of establishment of the culture ecology in the context of various direction. The modern times actualize specific processes of cultural studies ecologization,which in its turn is stipulated first ofall the fact that the traditional sphere of the cultural studies was "human-society", but the inclusion of the nature into the spiritual life sphere envisages the change of the modern societyparadigm, certain correction of world-view values and human consciousness. The methodological basis of the study is the concept, offered by D.Likhachov, which in relation to nature and culture requires general rules of moral awareness of oneself as a part of the nature and as a part of the culture, as well as the analysis of the culture ecology in the context of landscape approach, offered by V. Kaganskyi. Studying the historical-cultural landscapes,a famous cultural specialist D.Likhachovseesthe biosphere as a specific envelope ofthe Earth. He thinks about the cultural sphere as a certain historical "noosphere" of the planet, which has been performing the changing effect on the biosphere, that naturally required specific cultural study instruments. That is why in a very short period the cultural ecology has become a key factor in many biological, philosophical and cultural papers, which is supported by a large number of national and foreign researchers, who offer their own understanding of the cultural ecology. In the context of cultural ecology the landscape exists and is understood by different cultural practices and is a type of an abstract model, which cannot be touched and seen, it needs to be lived and experienced as the unity of space, things and meanings. V.Kaganskyi states that modern popularization of the monuments and culture protection results in a peculiar discarding of landscape, instead of experiencing it. In his analysis of various directions, V. Kaganskyi determines a special approach - geomorphism, which supports the variety of the cultural landscape places, as cultural value (where three components - landscape space, knowledge about it and experiencing it - are united). The main value of which is the value of inter-personal communication. This can be regarded as the creation of a new cultural reality, in which a person is immersed, and the cultural space becomes the landscape space (this is the unity of natural and cultural components, spatial forms and cultural meanings). Thus, the cultural landscape is seen as a phenomenon, which identifies itself, exists and is understood in different ways - in cultural practices, establishment of landmarks, which in general attracts the attention to the cultural knowledge, cultural ecology in particular, and stresses its importance in the modern culture.